A Three‐Dimensional Structure and Process Model for Integrated Hydro‐Geo‐Pedologic Analysis of a Constructed Hydrological Catchment. Issue 4 (14th November 2013) - Gerke, Horst H.; Maurer, Thomas; Schneider, Anna
Abstract : A structure model describes the boundary geometries and the three‐dimensional solid phase distributions of the catchment. In contrast to an established ecosystem, feedback relations can be assumed for an initial geosystem between the development of spatial structures and the water and element fluxes. The objective was to develop a hydrological catchment model as a three‐dimensional spatial database of the solid phase that allows an integrative analysis, a periodical mass balance, and the generation of distributed model parameters for the developing system. Data were from the constructed catchment "Chicken Creek." The initial texture and bulk density distributions were generated by imitating sediment dumping, segregation, and compaction. Boundary geometries and changes in surface topography due to erosion and sedimentation processes were quantified on the basis of digital elevation models (DEMs) derived from aerial photographs. The catchment was visualized with the three‐dimensional software GoCad; the "emergence" of the water table and other structures (e.g., soil horizons, root zone) could be spatially assigned and quantified to identify regions with specific processes. A combination of three‐dimensional catchment with time‐dependent two‐dimensional surface models allowed generating the development of spatially distributed erosion–deposition patterns that formed new initial surfaces. The three‐dimensional distributed solid phase structure of the catchment allowed for a more direct comparison with observations using minimal invasive methods. The mass balance of the solids could be related with pedologic development and transfer to other geopedologic systems achieved by adapting sediment transport and deposition in the descriptions of the model. This model may help improve the integrative analysis of hydrological catchments.